Youthful systemic milieu in younger recipients alleviates acute kidney injury via attenuating apoptosis and oxidative stress in a rat kidney transplantation model - Chengjun Yu; Jie Zhang; Jun Pei; Shengde Wu; Sheng Wen; Yi Hua; Guanghui Wei (PLoS ONE, 2025)
Purpose To evaluate whether acute kidney injury (AKI) differs between young and adult recipients and to explore the possible underlying mechanisms. Methods In an allogenic heterotopic rat kidney transplantation model, we evaluated the renal function, histological damage, oxidative stress injury, apoptosis, immune cell infiltration, and signaling pathways involved in young and adult recipients based on transcriptomics, proteomics, machine learning analyses, and experimental validation. We also identified and validated the possible hub immune-related genes and serum cytokines with the intersection of the maximal clique centrality method, betweenness centrality, and random forest algorithms. Results Younger recipients had lower levels of renal histological damage injury score, oxidative stress injury, and apoptosis. The cytokine profile was different in young and adult recipients. Cytokines and cytokine-mediated pathways involved in oxidative stress, apoptosis, proliferation, and immune cell infiltration were closely correlated with differentially expressed genes. In addition, cytokines mediated immune response participating in antioxidative, anti-apoptosis, and regeneration processes. Conclusions Younger systemic internal milieu in young recipients alleviated AKI after kidney transplantation by ameliorating oxidative stress and apoptosis via immune response regulation. Cytokines may play a protective role in AKI after kidney transplantation. The use of cytokines in transplantation deserves further experimental evaluation and clinical considerations.